2022
DOI: 10.3390/ma15124149
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ce, Ca, Fe, and Mn-Doped LaCoO3 Perovskite Oxide for the Four-Way Purification of PM, NOx, CO, and HC from Diesel Engine Exhaust

Abstract: Perovskite-type catalysts were widely used in the field of automobile exhaust purification due to their inherent physicochemical properties and excellent doping characteristics. A series of La1-xMxCo1-yNyO3 (M=Ce, Ca; N=Fe, Mn) perovskite-type catalyst samples were prepared by sol-gel method for the four-way purification of PM, NOx, CO, and HC emitted by diesel exhaust. The activity of catalyst samples was tested by simulation experiments and hydrogen temperature-programmed reduction (H2-TPR). Catalyst samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Cerium oxide is an excellent catalyst with abundant oxygen vacancies and strong interactions with other metals, so it is expected to be a promising substitute for the conventional lanthanum-based perovskite. Wu and Wang found that the catalysts prepared by partially replacing La with Ce increased the oxygen vacancy concentration of the catalyst, which also showed a large amount of α-O (adsorbed oxygen) desorption in O 2 -TPD characterization. The O ads /O latt ratio was also higher than that of the undoped or doped catalysts with other metal elements, which created conditions for good catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Cerium oxide is an excellent catalyst with abundant oxygen vacancies and strong interactions with other metals, so it is expected to be a promising substitute for the conventional lanthanum-based perovskite. Wu and Wang found that the catalysts prepared by partially replacing La with Ce increased the oxygen vacancy concentration of the catalyst, which also showed a large amount of α-O (adsorbed oxygen) desorption in O 2 -TPD characterization. The O ads /O latt ratio was also higher than that of the undoped or doped catalysts with other metal elements, which created conditions for good catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…26 Our previous studies showed that La 0.8 Ce 0.2 Fe 0.3 Co 0.7 O 3 can achieve the four-way purification of PM, NO x , CO and HC emitted by automobile exhausts, and the purification efficiency are 95%, 92%, 100%, and 94%, respectively. 27 In this work, biomorphic porous La 0.8 Ce 0.2 Fe 0.3 Co 0.7 O 3 perovskite-type catalysts were prepared by a facile bio-templating method taking wood fiber as template for achieving the four-way purification of PM, NO x , CO, and HC emitted by automobile exhausts.…”
Section: Introductionmentioning
confidence: 99%
“…Ming Zhou et al prepared biomorphic porous zinc oxide with wood fiber as template, which proved the specie of wood template and sintering temperature played vital roles in the pore size distribution, specific surface area, and pore volume of the product 26 . Our previous studies showed that La 0.8 Ce 0.2 Fe 0.3 Co 0.7 O 3 can achieve the four‐way purification of PM, NO x , CO and HC emitted by automobile exhausts, and the purification efficiency are 95%, 92%, 100%, and 94%, respectively 27 …”
Section: Introductionmentioning
confidence: 99%
“…[32] In addition, calcium is abundant and inexpensive, and its combination with transition metals such as Cr and Co, which have variable valences, can lead to effective physicochemical properties such as redox performance, oxygen mobility, ionic conductivity, etc. [33] The electrochemical performance of LaCaCoCrO 6 double perovskite has been compared with other double perovskites in Table 1. [34][35][36][37] In addition to the material used for the electrode, the electrolyte is critically important for electrochemical analysis.…”
Section: Introductionmentioning
confidence: 99%